Effects of stratospheric variability on El Niño teleconnections - Richter, Jadwiga (author); Deser, Clara (author); Sun, L. (author) (Environmental Research Letters, 2015)
The effects of the tropical Pacific El Niño Southern Oscillation (ENSO) phenomenon are communicated to the rest of the globe via atmospheric teleconnections. Traditionally, ENSO teleconnections have been viewed as tropospheric phenomena, propagating to higher latitudes as Rossby waves. Recent studies, however, suggest an influence of the stratosphere on extra-tropical ENSO teleconnections. The stratosphere is highly variable: in the tropics, the primary mode of variability is the quasi-biennial oscillation (QBO), and in the extra-tropics sudden stratospheric warmings (SSWs) regularly perturb the mean state. Here, we conduct a 10-member ensemble of simulations with a stratosphere-resolving atmospheric general circulation model forced with the observed evolution of sea surface temperatures during 1952-2001 to examine the effects of the QBO and SSWs on the zonal-mean circulation and temperature response to El Niño, with a focus on the northern extra-tropics during winter. We find that SSWs have a larger impact than the QBO on the composite El Niño responses. During El Niño winters with SSWs, the polar stratosphere shows positive temperature anomalies that propagate downward to the surface where they are associated with increased sea-level pressure over the Arctic. During El Niño winters without SSWs, the stratosphere and upper troposphere show negative temperature anomalies but these do not reach the surface. The QBO modulates the El Niño teleconnection primarily in winters without SSWs: the negative temperature anomalies in the polar stratosphere and upper troposphere are twice as large during QBO West compared to QBO East years. In addition, El Niño winters that coincide with the QBO West phase show stronger positive sea-level pressure anomalies over the eastern Atlantic and Northern Europe than those in the QBO East phase. The results imply that the stratosphere imparts considerable variability to ENSO teleconnections.